When Words Become a Trap - D. Klus-Stanska (Высшее образование в России)
The paper is an attempt to analyze the language of the Polish core curriculum for primary schools and the language of teaching methodology, created by the core curriculum, as a source of stereotype thinking about school and the (im)possibility of changing the model of education. In this perspective, the language of methodological documents appears as a significant barrier to changes in the educational system, perpetuating traditional teaching, and leading to the blocking of the development of students.